DNA damage induces nucleoid compaction via the Mre11-Rad50 complex in the archaeon Haloferax volcanii - Delmas, Stéphane; Duggin, Iain J.; Allers, Thorsten (Wiley, 2013)
In prokaryotes the genome is organized in a dynamic structure called the nucleoid, which is embedded in the cytoplasm. We show here that in the archaeon Haloferax volcanii, compaction and reorganization of the nucleoid is induced by stresses that damage the genome or interfere with its replication. The fraction of cells exhibiting nucleoid compaction was proportional to the dose of the DNA damaging agent, and results obtained in cells defective for nucleotide excision repair suggest that breakage of DNA strands triggers reorganization of the nucleoid. We observed that compaction depends on the Mre11-Rad50 complex, suggesting a link to DNA double-strand break repair. However, compaction was observed in a radA mutant, indicating that the role of Mre11-Rad50 in nucleoid reorganisation is independent of homologous recombination. We therefore propose that nucleoid compaction is part of a DNA damage response that accelerates cell recovery by helping DNA repair proteins to locate their targets, and facilitating the search for intact DNA sequences during homologous recombination.